Shield double-liquid synchronous grouting admixture and preparation method thereof
The dual-liquid simultaneous grouting additive for shield tunneling prepared by synthesizing workable mother liquor, water-retaining thickener, and retardant solves the problem of insufficient stability and homogeneity of traditional additives in construction of strata with different permeability coefficients. The stability and construction performance of grouting materials have been significantly improved.
Patent Information
- Application Number
- CN202411433785.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-10-15
AI Technical Summary
When traditional shield double-liquid grouting admixtures are constructed with different permeability coefficients, it is difficult to ensure the stability and homogeneity of grouting materials, and it is easy to cause the material to be diluted, internal structure damaged, unable to condense quickly, and aggravate the pipe sheet. The problem of floating phenomenon.
By synthesizing workability mother liquor, water-retaining thickener, and retardant, and adjusting the group ratio, a shield double-liquid simultaneous grouting admixture is prepared. This admixture uses silicate, expansion agent, and silicone polyether emulsion as active ingredients to stabilize the slurry system, maintain fluidity, avoid delamination problems, and improve the stability and construction performance of the grouting material.
This admixture can significantly improve the stability and adaptability of grouting materials, avoid segregation and delamination, and ensure that grouting materials have good construction performance and mechanical properties in strata with different permeability coefficients.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cement-based building material admixtures, in particular to a shield double-liquid synchronous grouting admixture and a preparation method thereof. Background Art
[0002] In the process of tunneling by shield method, since the outer diameter of the shield machine is larger than the outer diameter of the tunnel segment, a ring gap is left between the lining segment and the natural soil or rock layer after the shield machine passes. In order to prevent ground subsidence, slurry needs to be injected into the annular gap. The injected slurry plays a role in supporting the stratum, ensuring the stability of the early segment and improving the waterproof performance of the tunnel. Shield grouting is composed of cement, fly ash, bentonite, sand, water and admixtures. In order to achieve the requirements of pumpability and easy grouting, shield grouting needs to use slurry with high fluidity.
[0003] Shield grouting admixture is a mixed chemical additive that improves the performance of shield grouting materials. Shield grouting admixture is mainly used to improve the poor stability problem caused by the high fluidity of shield materials, regulate the setting time of shield grouting materials, and make the shield grouting materials impermeable and homogeneous.
[0004] However, traditional grouting processes often produce a large amount of waste and pollutants, posing potential harm to the environment. Therefore, the development of environmentally friendly grouting materials, such as synchronous dual-liquid grouting technology, can reduce the generation of waste, reduce the impact on the environment, and achieve the requirements of green construction. In the dual-liquid slurry technology, the cement-water glass dual-liquid slurry system has an ultra-short setting time and good early strength. Its excellent performance in controlling stratum settlement has attracted much attention in the industry. The main components of the cement-water glass dual-liquid slurry are liquid A and liquid B weighed and mixed according to the mix ratio, where liquid A is a cement-based pure slurry, mainly composed of cement, bentonite, and admixtures, and liquid B is a water glass solution.
[0005] In the prior art, traditional two-liquid grouting admixtures are prone to fail to achieve the desired construction effect when used in strata with different permeability coefficients. This is because the penetration rate of groundwater in strata with different permeability coefficients is different, the grouting material is diluted, its internal structure is destroyed, and the material cannot condense quickly, which will aggravate the floating phenomenon of the pipe segments during construction. The high-efficiency water-reducing agent used in traditional two-liquid grouting admixtures is not adaptable enough to this situation, and cannot guarantee the homogeneity and stability of the grouting material, and to a certain extent, it also aggravates the segregation of the grouting material. Summary of the invention
[0006] In order to solve the problems in the prior art, the present invention provides a shield double-liquid synchronous grouting admixture, which is synthesized by a workability mother liquor, a water-retaining thickener and a retarder. The workability mother liquor can solve the problems of poor workability of grouting materials and rapid loss of working performance by adjusting the group ratio. The water-retaining thickener can stabilize the slurry system, maintain the flow performance, and avoid the problem of stratification of the grouting materials. The synthetic environment can synergistically improve the stability of the grouting materials under the condition of ensuring the setting time. The admixture is combined with silicate, expansion agent, and silicone resin polyether emulsion as effective ingredients. The prepared admixture can not only improve the adaptability of the grouting material to formations with different permeability coefficients, enhance the stability of the grouting material, and prevent water from being separated, but also does not affect the development of the mechanical properties of the grouting material.
[0007] Specifically, the shield double-liquid synchronous grouting admixture of the present invention is composed of the following raw materials in parts by weight: 2-7 parts of workability mother solution, 1-5 parts of water-retaining thickener, 15-30 parts of retarder, 1-5 parts of silicate, 1-5 parts of expansion agent, 1-3 parts of silicone resin polyether emulsion, and 47-72 parts of water.
[0008] Preferably, the workability mother solution is polymerized from 300-340 parts of polyether macromonomer, 45-55 parts of acrylic acid, and 8-12 parts of hydroxypropyl acrylate. The workability mother solution of the present invention effectively improves the adsorption of calcium ions on the surface of cement particles by adjusting the composition of organic groups, increases the number of anchoring groups, increases adsorption, and has a large steric hindrance effect, thereby ensuring the stability and homogeneity of the material in a high-fluidity grouting liquid system.
[0009] Preferably, the water-retaining thickener is polymerized from 100-120 parts of acrylic acid, 70-90 parts of acrylamide, 20-30 parts of polyether macromonomer, and 8-12 parts of 2-hydroxyethyl acrylate. After the carboxylic acid of the water-retaining thickener of the present invention is ionized, carboxylate anions are formed and charged. Under the repulsive force between the same charges, the macromolecular chains are opened to form a network structure, and water molecules are adsorbed, so that the fluidity of the system decreases, the viscosity increases, and the thickening effect is obtained, thereby stabilizing the grouting material system, allowing the synchronous grouting material to maintain stability in water-rich strata with large permeability coefficients, and improving the stratification problem that has occurred in traditional grouting materials. In addition, the present invention uses a water-retaining thickener and a silicone resin polyether emulsion for composite use, which can better improve the stability of shield materials under construction in strata with different permeability coefficients and ensure the construction performance of shield materials.
[0010] Preferably, the retarder is polymerized from 300-400 parts of polyether macromonomer, 40-50 parts of acrylic acid, 80-100 parts of AMPS, and 20-40 parts of itaconic acid. Conventional retarders in shield materials mainly include organic phosphoric acid (salt), borax (acid) compound, hydroxy phosphoric acid (salt) compound, etc. Although these materials are cheap and easy to obtain and have good retarding effect, they all have a certain negative impact on the performance of cement slurry. The present invention adopts a self-developed retarder, which has good temperature and salt resistance, controllable product performance, low dosage sensitivity, and adsorbs Ca on cement surface particles. 2+ The capacity is increased, the retarding effect is enhanced, the setting time is adjustable, and the requirement of small loss of working performance is met within the setting time, and finally high water resistance and dispersibility are achieved without causing loss of grouting fluid strength.
[0011] More preferably, the process for preparing the workable mother solution is:
[0012] a. Add 300-340 parts of polyether macromonomer and 470-490 parts of solvent to the reactor, stir evenly, add 8-12 parts of hydroxypropyl acrylate, 9-12 parts of sodium hypophosphite, 4-6 parts of ferrous sulfate solution, most of acrylic acid, 8-9 parts of hydrogen peroxide, stir evenly,
[0013] b. Mix the remaining acrylic acid, 2-3 parts of mercaptopropionic acid, and 8-10 parts of solvent to obtain material A, and mix 1-2 parts of vitamin C and 7-9 parts of solvent to obtain material B.
[0014] c. Add material A and material B dropwise into the reaction kettle, keep warm, adjust the pH value to 5-7, and cool to obtain.
[0015] Preferably, the temperature of the reactor in step a is 40-45° C., the dropwise addition time of material A in step c is 1.5-2 h, the dropwise addition time of material B is 1.5-2 h, and the temperature is kept for 1-2 h after the dropwise addition of materials AB is completed.
[0016] More preferably, the preparation process of the water-retaining thickener is:
[0017] ①. Add 70-90 parts of acrylamide and 470-490 parts of solvent to the reactor, stir evenly, add 20-30 parts of polyether macromonomer, 8-12 parts of 2-hydroxyethyl acrylate, mix evenly, then add 1-2 parts of thioglycolic acid, 2-3 parts of sodium bisulfite, 7-8 parts of ammonium persulfate, most of the acrylic acid, stir evenly,
[0018] ②. Evenly mix the remaining acrylic acid and 7-9 parts of solvent to obtain material C, and evenly mix 2-3 parts of vitamin C and 9-10 parts of solvent to obtain material D.
[0019] ③. Add material C and material D dropwise into the reaction kettle, keep warm, adjust the pH value to 6-7, and cool to obtain.
[0020] Preferably, in step ①, the temperature of the reactor is 55-65° C., in step ③, the dropwise addition time of material C is 1-1.5 h, the dropwise addition time of material D is 1.5-2 h, and after the dropwise addition of material CD is completed, the mixture is kept warm for 1-2 h.
[0021] More preferably, the retarder preparation process is:
[0022] i) Add 300-400 parts of polyether macromonomer, 20-40 parts of itaconic acid, 80-100 parts of AMPS, and 370-520 parts of solvent to the reaction kettle, stir evenly, add 5-10 parts of sodium hypophosphite, stir evenly,
[0023] ii) 45-55 parts of acrylic acid and 9-11 parts of solvent are mixed evenly to obtain material E, and 5-7 parts of ammonium persulfate and 8-10 parts of solvent are mixed evenly to obtain material F.
[0024] iii) Add material E and material F dropwise into the reaction kettle, keep warm, and cool to obtain the product.
[0025] Preferably, in step i), the temperature of the reactor is 55-60° C., in step iii), the E material is added dropwise for 1-1.5 h, the F material is added dropwise for 0.5-1 h, and the EF material is kept warm for 2-3 h after the addition is completed.
[0026] Preferably, the solvent is deionized water.
[0027] Preferably, the silicate is at least one of potassium silicate, sodium silicate and lithium silicate.
[0028] Preferably, the expansion agent is a plastic expansion agent.
[0029] Preferably, the polyether macromonomer is at least one of TPEG and EPEG.
[0030] The present invention also relates to a method for preparing the above-mentioned shield double-liquid synchronous grouting admixture, which specifically comprises the following steps:
[0031] 1) Weigh each raw material by weight,
[0032] 2) Add water, workability mother solution, water-retaining thickener, retarder, silicate, expansion agent and silicone resin polyether emulsion into the mixer in sequence and mix well to obtain the product.
[0033] The invention also relates to the application of a shield double-liquid synchronous grouting admixture, and specifically, the addition amount is 0.8-2% of the mass of the cementitious material.
[0034] The grouting material using the shield double-liquid grouting admixture of the present invention has a good dispersion effect, the stability of the grouting material is significantly improved, it is not easy to segregate and delaminate, and has good strength stability. DETAILED DESCRIPTION
[0035] In order to characterize the technical effect of the present invention, the preparation method of the present invention is adopted to change the raw material ratio to prepare the shield double-liquid synchronous grouting admixture, add it to the grouting material and test the performance of the grouting material, wherein the expansion agent adopts the polar bear CSA plastic expansion agent. During the test, the grouting material ratio is: A liquid: 400 parts of P·O42.5 cement, 150 parts of bentonite, 4 parts of grouting admixture, 700 parts of water, B liquid: 47.6L of water glass.
[0036] Example 1
[0037] The shield double-liquid synchronous grouting admixture is composed of the following raw materials in parts by weight: 5 parts of workability mother liquor, 4 parts of water-retaining thickener, 25 parts of retarder, 2 parts of sodium silicate, 4 parts of expansion agent, 1 part of silicone resin polyether emulsion, and 55 parts of water.
[0038] The preparation process of workability mother liquor is as follows:
[0039] a. Add 320 parts of TPEG, 470 parts of deionized water to the reactor, stir evenly, add 10 parts of hydroxypropyl acrylate, 10 parts of sodium hypophosphite, 5 parts of ferrous sulfate solution, 45 parts of acrylic acid, 8 parts of hydrogen peroxide, stir evenly,
[0040] b. Mix 5 parts of acrylic acid, 2 parts of mercaptopropionic acid, and 8 parts of deionized water to obtain material A. Mix 1.5 parts of vitamin C and 8 parts of deionized water to obtain material B.
[0041] c. Add material A and material B dropwise to the reactor at 1.5h, keep warm for 1.5h, adjust the pH value to 7, and cool to obtain.
[0042] The preparation process of water-retaining thickener is:
[0043] ① Add 90 parts of acrylamide and 480 parts of deionized water to the reactor, stir evenly, add 25 parts of EPEG, 9 parts of 2-hydroxyethyl acrylate, mix evenly, then add 1.5 parts of thioglycolic acid, 2 parts of sodium bisulfite, 8 parts of ammonium persulfate, 100 parts of acrylic acid, stir evenly,
[0044] ②. Mix 10 parts of acrylic acid and 8 parts of deionized water to obtain material C. Mix 3 parts of vitamin C and 10 parts of deionized water to obtain material D.
[0045] ③. Add material C at 1h and material D at 1.5h to the reactor, keep warm for 2h, adjust the pH value to 7, cool and obtain.
[0046] The preparation process of retarder is:
[0047] i) Add 380 parts of TPEG, 30 parts of itaconic acid, 90 parts of AMPS, and 450 parts of deionized water to the reactor, stir evenly, add 7 parts of sodium hypophosphite, stir evenly,
[0048] ii) Mix 55 parts of acrylic acid and 10 parts of deionized water to obtain material E, and mix 5 parts of ammonium persulfate and 8 parts of deionized water to obtain material F.
[0049] iii) Add material E and material F dropwise into the reaction kettle at 1 h, keep warm for 3 h, and cool to obtain the product.
[0050] After testing, the initial fluidity of the grouting material was 275mm, the stratification was 3mm, the water seepage rate was 1.71%, and the 28d compressive strength was 38.3MPa.
[0051] Example 2
[0052] The shield double-liquid synchronous grouting admixture is composed of the following raw materials by weight: 7 parts of workability mother liquid, 5 parts of water-retaining thickener, 24 parts of retarder, 3 parts of silicate, 2 parts of expansion agent, 2 parts of silicone resin polyether emulsion, 60 parts of water,
[0053] The preparation process of workability mother liquor is as follows:
[0054] a. Add 300 parts of EPEG and 470 parts of deionized water to the reactor, stir evenly, add 12 parts of hydroxypropyl acrylate, 11 parts of sodium hypophosphite, 6 parts of ferrous sulfate solution, 45 parts of acrylic acid, 8.5 parts of hydrogen peroxide, stir evenly,
[0055] b. Mix 8 parts of acrylic acid, 2.5 parts of mercaptopropionic acid, and 9 parts of deionized water to obtain material A. Mix 2 parts of vitamin C and 7 parts of deionized water to obtain material B.
[0056] c. Add material A and material B dropwise to the reactor at 1.5h, keep warm for 1.5h, adjust the pH value to 7, and cool to obtain.
[0057] The preparation process of water-retaining thickener is:
[0058] ① Add 80 parts of acrylamide and 470 parts of deionized water to the reactor, stir evenly, add 28 parts of TPEG, 11 parts of 2-hydroxyethyl acrylate, mix evenly, then add 2 parts of thioglycolic acid, 3 parts of sodium bisulfite, 8 parts of ammonium persulfate, 100 parts of acrylic acid, stir evenly,
[0059] ②. Mix 6 parts of acrylic acid and 7 parts of deionized water to obtain material C. Mix 3 parts of vitamin C and 10 parts of deionized water to obtain material D.
[0060] ③. Add material C at 1h and material D at 1.5h to the reactor, keep warm for 2h, adjust the pH value to 7, cool and obtain.
[0061] The preparation process of retarder is:
[0062] i) Add 370 parts of polyether macromonomer, 40 parts of itaconic acid, 100 parts of AMPS, and 490 parts of deionized water to the reactor, stir evenly, add 7 parts of sodium hypophosphite, stir evenly,
[0063] ii) 55 parts of acrylic acid and 11 parts of deionized water were mixed evenly to obtain material E, and 6 parts of ammonium persulfate and 9 parts of deionized water were mixed evenly to obtain material F.
[0064] iii) Add material E and material F dropwise into the reaction kettle at 1 h, keep warm for 3 h, and cool to obtain the product.
[0065] After testing, the initial fluidity of the grouting material was 270mm, the stratification was 2mm, the water seepage rate was 1.65%, and the 28d compressive strength was 38.6MPa.
[0066] Comparative Example 1
[0067] The grouting admixture is composed of the following raw materials in parts by weight: 5 parts of our company's SR type polycarboxylic acid slow-release mother solution, 4 parts of water-retaining thickener, 25 parts of retarder, 2 parts of sodium silicate, 4 parts of expansion agent, 1 part of silicone resin polyether emulsion, and 55 parts of water.
[0068] The preparation process of the water-retaining thickener and retarder is the same as that of Example 1.
[0069] After testing, the initial fluidity of the grouting material was 230mm, the stratification was 7mm, the water seepage rate was 3.64%, and the 28d compressive strength was 30.2MPa.
[0070] Comparative Example 2
[0071] The grouting admixture is composed of the following raw materials in parts by weight: 5 parts of workability mother solution, 4 parts of hydroxypropyl methylcellulose ether, 25 parts of retarder, 2 parts of sodium silicate, 4 parts of expansion agent, 1 part of silicone resin polyether emulsion, and 55 parts of water.
[0072] The preparation process of workability mother solution and retarder is the same as that in Example 1.
[0073] After testing, the initial fluidity of the grouting material was 250mm, the stratification was 10mm, the water seepage rate was 3.98%, and the 28d compressive strength was 27.5MPa.
[0074] Comparative Example 3
[0075] The grouting admixture is composed of the following raw materials in parts by weight: 5 parts of workability mother solution, 4 parts of water-retaining thickener, 25 parts of hydroxyethylidene diphosphonic acid, 2 parts of sodium silicate, 4 parts of expansion agent, 1 part of silicone resin polyether emulsion, and 55 parts of water.
[0076] The preparation process of workability mother solution and water-retaining thickener is the same as that in Example 1.
[0077] After testing, the initial fluidity of the grouting material was 240mm, the stratification was 8mm, the water seepage rate was 3.22%, and the 28d compressive strength was 25.5MPa.
[0078] Comparative Example 4
[0079] The grouting admixture is composed of the following raw materials in parts by weight: 5 parts of workability mother solution, 4 parts of water-retaining thickener, 25 parts of retarder, 2 parts of sodium silicate, 4 parts of expansion agent, and 55 parts of water.
[0080] The preparation process of workability mother solution, water-retaining thickener and retarder is the same as that of Example 1.
[0081] After testing, the initial fluidity of the grouting material was 260mm, the stratification was 9mm, the water seepage rate was 3.06%, and the 28d compressive strength was 27.3MPa.
[0082] Comparative Example 5
[0083] The grouting admixture is composed of the following raw materials in parts by weight: 5 parts of workability mother solution, 4 parts of water-retaining thickener, 25 parts of retarder, 2 parts of sodium silicate, 4 parts of expansion agent, 1 part of silicone resin polyether emulsion, and 55 parts of water.
[0084] The preparation process of workability mother liquor is as follows:
[0085] a. Add 360 parts of TPEG, 470 parts of deionized water to the reactor, stir evenly, add 5 parts of hydroxypropyl acrylate, 10 parts of sodium hypophosphite, 5 parts of ferrous sulfate solution, 40 parts of acrylic acid, 8 parts of hydrogen peroxide, stir evenly,
[0086] b. Mix 5 parts of acrylic acid, 2 parts of mercaptopropionic acid, and 8 parts of deionized water to obtain material A. Mix 1.5 parts of vitamin C and 8 parts of deionized water to obtain material B.
[0087] c. Add material A and material B dropwise to the reactor at 1.5h, keep warm for 1.5h, adjust the pH value to 7, and cool to obtain.
[0088] The preparation process of water-retaining thickener is:
[0089] ①. Add 100 parts of acrylamide and 480 parts of deionized water to the reactor, stir evenly, add 40 parts of EPEG, 6 parts of 2-hydroxyethyl acrylate, mix evenly, then add 1.5 parts of thioglycolic acid, 2 parts of sodium bisulfite, 8 parts of ammonium persulfate, 100 parts of acrylic acid, stir evenly,
[0090] ②. Mix 10 parts of acrylic acid and 8 parts of deionized water to obtain material C. Mix 3 parts of vitamin C and 10 parts of deionized water to obtain material D.
[0091] ③. Add material C at 1h and material D at 1.5h to the reactor, keep warm for 2h, adjust the pH value to 7, cool and obtain.
[0092] The preparation process of the retarder is the same as that of Example 1.
[0093] After testing, the initial fluidity of the grouting material was 250mm, the stratification was 8mm, the water seepage rate was 3.49%, and the 28d compressive strength was 24.6MPa.
[0094] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A shield double-liquid synchronous grouting admixture, characterized in that: The invention is composed of the following raw materials in parts by weight: 2-7 parts of workability mother solution, 1-5 parts of water-retaining thickener, 15-30 parts of retarder, 1-5 parts of silicate, 1-5 parts of expansion agent, 1-3 parts of silicone resin polyether emulsion, 47-72 parts of water, The workability mother solution is polymerized from 300-340 parts of polyether macromonomer, 45-55 parts of acrylic acid, and 8-12 parts of hydroxypropyl acrylate. The water-retaining thickener is polymerized from 100-120 parts of acrylic acid, 70-90 parts of acrylamide, 20-30 parts of polyether macromonomer, and 8-12 parts of 2-hydroxyethyl acrylate. The retarder is prepared by polymerization of 300-400 parts of polyether macromonomer, 45-55 parts of acrylic acid, 80-100 parts of AMPS and 20-40 parts of itaconic acid. The polyether macromonomer is at least one of TPEG and EPEG.
2. The shield double-liquid synchronous grouting admixture according to claim 1, characterized in that: The process for preparing the workable mother solution is as follows: a. Add 300-340 parts of polyether macromonomer and 470-490 parts of solvent to the reactor, stir evenly, add 8-12 parts of hydroxypropyl acrylate, 9-12 parts of sodium hypophosphite, 4-6 parts of ferrous sulfate solution, most of acrylic acid, 8-9 parts of hydrogen peroxide, stir evenly, b. Mix the remaining acrylic acid, 2-3 parts of mercaptopropionic acid, and 8-10 parts of solvent to obtain material A, and mix 1-2 parts of vitamin C and 7-9 parts of solvent to obtain material B. c. Add material A and material B dropwise into the reaction kettle, keep warm, adjust the pH value to 5-7, and cool to obtain.
3. The shield double-liquid synchronous grouting admixture according to claim 2 is characterized in that: The temperature of the reactor in step a is 40-45° C., the dropwise addition time of material A in step c is 1.5-2 h, the dropwise addition time of material B is 1.5-2 h, and the temperature is kept for 1-2 h after the dropwise addition of materials AB is completed.
4. The shield double-liquid synchronous grouting admixture according to claim 1, characterized in that: The preparation process of the water-retaining thickener is as follows: ①. Add 70-90 parts of acrylamide and 470-490 parts of solvent to the reactor, stir evenly, add 20-30 parts of polyether macromonomer, 8-12 parts of 2-hydroxyethyl acrylate, mix evenly, then add 1-2 parts of thioglycolic acid, 2-3 parts of sodium bisulfite, 7-8 parts of ammonium persulfate, most of the acrylic acid, stir evenly, ②. Evenly mix the remaining acrylic acid and 7-9 parts of solvent to obtain material C, and evenly mix 2-3 parts of vitamin C and 9-10 parts of solvent to obtain material D. ③. Add material C and material D dropwise into the reaction kettle, keep warm, adjust the pH value to 6-7, and cool to obtain.
5. The shield double-liquid synchronous grouting admixture according to claim 4, characterized in that: In step ①, the temperature of the reactor is 55-65° C., in step ③, the dropping time of material C is 1-1.5 h, the dropping time of material D is 1.5-2 h, and after the dropping of material CD is completed, the temperature is kept for 1-2 h.
6. The shield double-liquid synchronous grouting admixture according to claim 1, characterized in that: The retarder preparation process is: i) Add 300-400 parts of polyether macromonomer, 20-40 parts of itaconic acid, 80-100 parts of AMPS, and 370-520 parts of solvent to the reaction kettle, stir evenly, add 5-10 parts of sodium hypophosphite, stir evenly, ii) 45-55 parts of acrylic acid and 9-11 parts of solvent are mixed evenly to obtain material E, and 5-7 parts of ammonium persulfate and 8-10 parts of solvent are mixed evenly to obtain material F. iii) Add material E and material F dropwise into the reaction kettle, keep warm, and cool to obtain the product.
7. The shield double-liquid synchronous grouting admixture according to claim 6, characterized in that: In step i), the temperature of the reactor is 55-60° C., in step iii), the time for adding material E is 1-1.5 h, the time for adding material F is 0.5-1 h, and after the addition of material EF is completed, the temperature is kept for 2-3 h.
8. The shield double-liquid synchronous grouting admixture according to any one of claims 2 to 7, characterized in that: The solvent is deionized water.
9. The shield double-liquid synchronous grouting admixture according to claim 1, characterized in that: The silicate is at least one of potassium silicate, sodium silicate and lithium silicate, and the expansion agent is a plastic expansion agent.
10. The method for preparing the shield double-liquid synchronous grouting admixture according to any one of claims 1 to 9, characterized in that: The steps include: 1) Weigh each raw material by weight, 2) Add water, workability mother solution, water-retaining thickener, retarder, silicate, expansion agent and silicone resin polyether emulsion into the mixer in sequence and mix well to obtain the product.
Citation Information
Patent Citations
Slump-retaining polycarboxylic acid powder and preparation method thereof
CN108164661A
High-slump-loss-resistant synergist and preparation method and application thereof
CN109879629A
Regenerated wet-mixed mortar admixture and preparation method thereof
CN117209201A